Fugitive dust emissions from off-road vehicle maneuvers on military training lands - Meeks, Jeremy C. (Kansas State University, 2013)
Military installations in the United States may be large sources of fugitive dust emissions. Off-road vehicle training can contribute to air quality degradation resulting from increased wind erosion events as a result of soil disruption; however, limited information exists regarding the impacts of off-road vehicle maneuvering. This study was conducted to determine the effects of soil texture and intensity of training with off-road vehicles on fugitive dust emission potential due to wind erosion at military training installations. Multi-pass trafficking experiments, involving wheeled and tracked military vehicles (i.e., M1A1 Abrams tank, M925A1 water tanker and various HMMWV models), were conducted at three military training facilities with different climate and soil texture (i.e., Fort Riley, KS; Fort Benning, GA; and Yakima Training Center, WA). Dust emissions were measured on site using a Portable In-Situ Wind Erosion Laboratory (PI-SWERL) coupled with a DustTrak™ dust monitor. In addition, a top layer of soil was collected in trays and tested in a laboratory wind tunnel for dust emission potential. In wind tunnel testing, the amount of emitted dust was measured using glass-fiber filters through high-volume samplers. Also, the particle size distribution and concentration of the emitted dust were measured using a GRIMM aerosol spectrometer. Comparison of the PI-SWERL (with DustTrak™ dust monitor) and wind tunnel test (with GRIMM aerosol spectrometer) results showed significant difference and little correlation. Also, comparison of the filter and GRIMM aerosol spectrometer data showed significant difference but high correlation. The dust emission potential (as measured with the GRIMM spectrometer) was significantly influenced by soil texture, vehicle type and number of passes. For the light-wheeled vehicle, total dust emissions increased from 66 mg m-2 for undisturbed soil to 304 mg m-2 (357%) and 643 mg m-2 (868%) for 10 and 50 passes, respectively. For the tracked vehicle, an average increase in total dust emission of 569% was observed between undisturbed conditions and 1 pass, with no significant increase in emissions potential beyond 1 pass. For the heavy-wheeled vehicle, emissions increased from 75 mg m-2 for undisturbed soil to 1,652 mg m-2 (1,369%) and 4,023 mg m-2 (5,276%) for 10 and 20 passes, respectively. Soil texture also played an important role in dust emission potential. For all treatment effects, there was a 1,369% difference in emissions between silty clay loam soil and loamy sand soil.
Keywords: Wind erosion; Soil; Particulate matter; Dust; Engineering, Agricultural (0539); Environmental Engineering (0775); Soil Sciences (0481)